Recent Advances in Nanogenerators (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This book focuses on both fundamental and applied research on nanogenerators. The triboelectric nanogenerator (TENG) is based on expanded Maxwell’s equations for a mechano-driven system, including the polarization density term Ps in a displacement vector owing to the electrostatic charges on medium surfaces as produced by effects such as triboelectrification. The TENGs have potential applications in blue energy, wearable devices, environmental protectioin, medical science, and security. Hybridized and coupled nanogenerators further expand the application of nanogenerators in energy stability and multi-functional sensing.